IMPLEMENTASI KEBIJAKAN PEMERINTAH KABUPATEN BANYUWANGI DALAM PENANGANAN HIV DAN AIDS DI KABUPATEN BANYUWANGI - Novia Qurrota Ayun; Hary Priyanto; Erna Agustina (Yayasan Nusantara Hasana Berdikari, 2025)
Rapid development in Banyuwangi Regency has presented a serious challenge in the form of increasing HIV and AIDS cases. This phenomenon is ironic for a region currently transforming into a leading tourist destination, and also illustrates the gap between the success of physical development and the community's social preparedness to face its negative impacts. The increasing number of people living with HIV (PLWHA) is not only a health issue but also an indicator of systemic failure in social protection and the effectiveness of public policies. This research is based on a qualitative descriptive approach. The purpose of the study is to describe and analyze the role of the Banyuwangi Regency Health Office, as the leading sector of the Banyuwangi Regency Government, in implementing Regional Regulation Number 5 of 2017 on HIV and AIDS management in Banyuwangi Regency. The study concludes that the implementation of Regional Regulation Number 5 of 2017 by the Banyuwangi Regency Health Office in addressing HIV and AIDS has been structured through a collaborative and integrative approach. However, significant challenges remain, such as the high number of PLWHA cases in Banyuwangi Regency, social stigma against PLWHA, limited access to health services, and suboptimal education and community participation.